Sekolah Ramah Anak: Pentingnya Kerjasama Dan Peran Keluarga, Masyarakat, Dan Sekolah Dalam Pendidikan - Amanda, Dila Tiva; Muallifatul Khorida Filasofa, Lilif (Program Studi Pendidikan Islam Anak Usia Dini, 2025)
This research aims to find out the importance of cooperation and the role of family, school and society in education. The research method used in this paper is the library research method where the source of material is obtained based on references from books, journals, articles related to the theme discussed. The co-operation of families, schools and communities is very important in the development of child-friendly schools. Families, schools and communities significantly influence education. Families create the foundation for education, build character and provide moral values. They support children emotionally, financially and academically. Schools offer structured learning and socialisation opportunities, while communities contribute through support and innovation. By working together, it will support the education process in children.